Digital Political Branding dan Agenda-Setting dalam Pemilihan Presiden Indonesia 2024: Analisis Kampanye Prabowo-Gibran - Lubis, Muhammad Ridwan; Dianto, Icol (PT Anugerah Literasi Indomedia, 2025)
This research is motivated by the dominance of digital campaigns in the 2024 Indonesian Presidential Election and the need to understand how the construction of candidate images through personal branding and visual strategies affects the behavior of young voters. This study analyzes Prabowo-Gibran's political marketing strategy through four main elements: image transformation through personal digital branding